Taste disorders: A review - Vijay Kumar Ambaldhage; Jaishankar Homberhalli Puttabuddi; Purnachandrarao Naik Nunsavath; Yehoshuva R Tummuru (Wolters Kluwer Medknow Publications, 2014)
For maintenance of the health of an individual, taste sensation is very important. It is an important sensation that serves to assess the nutritious content of food, support oral intake, and prevent ingestion of potentially toxic substances. Disturbances in the perception of taste can lead to loss of appetite, causing malnutrition and thus distressing both the physical and psychological well-being of the patient. Oral physicians are often the first clinicians who hear complaints about alteration in taste from the patients. In spite of the effect of taste changes on health, literature on the diagnosis, pathogenesis, and precise treatment of taste disorders are less. Taste changes may lead patients to seek inappropriate dental treatments. Proper diagnosis of the etiology is the foremost step in the treatment of taste disorders. Thus, it is important that dental clinicians to be familiar with the various causes and proper management of taste changes. In this article, we have reviewed related articles focusing on taste disorders and their management, to provide a quick sketch for the clinicians. A detailed search was performed to identify the systematic reviews and research articles on taste disorders, using PUBMED and Cochrane. All the authors independently extracted data for analysis and review. Ultimately, 26 articles underwent a full text review. In conclusion, the research to date certainly offers us valid management strategies for taste disorders. Meanwhile, practical strategies with the highest success are needed for further intervention.